How to Escape from Model Platonism in Economics: Critical Assumptions, Robust Conclusions, and Approximate Explanations - Max Albert (Homo Oeconomicus, 2022)
About sixty years ago, Hans Albert criticized economists for their "model platonism", a methodological attitude that immunizes theoretical models against empirical criticism. Since then, economics has taken an empirical turn; yet, model platonism lingers on. The root of the problem is economists' reluctance to distinguish explicitly between the law-like and the situational assumptions of their models. Without this distinction, it is impossible to give a satisfactory account of the interplay between theory and empirical investigations. Based on Hans Albert's critical rationalism, the paper explains how making the distinction allows economists to escape from model platonism. By identifying critical situational assumptions and robust conclusions, economists can, and sometimes do, find approximate explanations even though they cannot completely avoid unrealistic simplifications.
Keywords: B41; 330; Approximate explanations; Critical rationalism; Model platonism; Robustness; Critical assumptions; Unrealistic assumptions